Dimensions of Ethnocentric Emotions in Hungary - Csatáriné Dogi, Ilona (International Journal of Engineering and Management Sciences, 2018)
The concept ot ethnocentrism appeared first in the literature in the early 1900s. Since then, several international and national studies have focused on defining this concept and have aimed at the investigation of its role in terms of national and international product opinion. The consumer’s decision is influenced not only by the different marketing effects (product, price, place, promotion), but also by the cultural, social, personal and psychological characteristics of the costumers. The examination of ethnocentrism – as a socio-psychological concept – is increasingly important in marketing research. This paper focuses on exploring the dimensions of ethnocentric emotions. My aim is to support the assumption that these dimensions have a significant influence on the thinking of the consumer society. As a result of my primary research, I introduce these dimensions and terminate consumer segments. Based on my research it can be stated that the ethnocentric emotions (such as patriotism, national superiority, national consciousness, national discrimination) are determinants of consumer thinking and demonstrate the fact that awareness of ethnocentric emotions can be the basis for marketing strategies to protect national products.